Immunization coverage in children of 24-35 months of age group in rural field practice areas of medical college, Visnagar, Gujarat, India: a cross sectional study - Joshi, Maulik D.; Nimbalkar, Dhruv P.; Thakor, Nilesh (International Journal Of Community Medicine And Public Health, 2022)
Background: Immunization plays a crucial role in reducing childhood morbidity and mortality, and higher coverage rates are needed to maintain the expected benefits. Objective was to assess immunization coverage in children of 12-23 months of age group in rural field practice areas of Medical College, Visnagar, Gujarat, India. Methods: Using the purposive sampling method, a cross sectional community based study was conducted in rural field practice areas of Nootan Medical College and Research Center, Visnagar during June 2021 to December 2021. All 214 children of 24-35 months age group of the areas were included after taking verbal informed consent of their parents or guardians. Vaccination status of the children was verified using the immunization card. Analysis of study was done by using appropriate statistical software. Results: Total 1934 households were surveyed. There were 214 children in the 24-35 months age group. Mamta card or immunization record was available with 145 (67.8%) mothers of 24-35 months age group of children. Maximum coverage was seen for bacille Calmette-Guerin (BCG) (96.7%) followed by pentavalent/RVV/OPV first dose (95.8%). Measles-Rubella (MR) 2nd dose coverage was 84.6%. Overall, 75.7% of the children in the 24-35 months age group were completely immunized while only 6 children were unimmunized. Dropout rate proportion for pentavalent 1st dose to pentavalent 3rd dose was 3.44% while for BCG first dose to MR second dose was 12.51%. Conclusions: Complete immunization coverage in children of 24-35 months of age group in rural field practice areas of Medical College, Visnagar was 75.7%.